115k views
2 votes
14. 9(y - 4) - 7y = 5(3y - 2
step by step please​

User Pmishev
by
5.2k points

2 Answers

4 votes

Answer:

y=-2

Explanation:

Simplifying

9(y + -4) + -7y = 5(3y + -2)

Reorder the terms:

9(-4 + y) + -7y = 5(3y + -2)

(-4 * 9 + y * 9) + -7y = 5(3y + -2)

(-36 + 9y) + -7y = 5(3y + -2)

Combine like terms: 9y + -7y = 2y

-36 + 2y = 5(3y + -2)

Reorder the terms:

-36 + 2y = 5(-2 + 3y)

-36 + 2y = (-2 * 5 + 3y * 5)

-36 + 2y = (-10 + 15y)

Solving

-36 + 2y = -10 + 15y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-15y' to each side of the equation.

-36 + 2y + -15y = -10 + 15y + -15y

Combine like terms: 2y + -15y = -13y

-36 + -13y = -10 + 15y + -15y

Combine like terms: 15y + -15y = 0

-36 + -13y = -10 + 0

-36 + -13y = -10

Add '36' to each side of the equation.

-36 + 36 + -13y = -10 + 36

Combine like terms: -36 + 36 = 0

0 + -13y = -10 + 36

-13y = -10 + 36

Combine like terms: -10 + 36 = 26

-13y = 26

Divide each side by '-13'.

y = -2

Simplifying

y = -2

User SamJackSon
by
6.1k points
5 votes

Answer:

y=-2

Explanation:

9(y−4)−7y=5(3y−2)

(9)(y)+(9)(−4)+−7y=(5)(3y)+(5)(−2)

9y+−36+−7y=15y+−10

(9y+−7y)+(−36)=15y−10

2y+−36=15y−10

2y−36=15y−10

Step 2:

2y−36−15y=15y−10−15y

−13y−36=−10

Step 3:

−13y−36+36=−10+36

−13y=26

divide

/13 /13

y=-2

User ASten
by
4.9k points